Peran Psikologi dalam Pendidikan Kristen di Sekolah Kristen - Hardi Budiyana (Jurnal Pendidikan Agama Kristen (JUPAK), 2020)
Christian education is a teaching and learning process that is based on the Bible, is moved by the Holy Spirit, and is Christocentric. One of the formal Christian education is manifested in Christian schools. Christian education in Christian schools is certainly different from education in schools in general. The Christian education, which is Christian and based on the Bible, is what distinguishes Christian schools from schools in general. Through a descriptive qualitative approach, the writer wants to describe the purpose of the role of educational psychology in Christian education. Where Christian education is to equip students in science, character and attitudes according to the Bible, but Christian education in schools also aims to bring students to become disciples of the Lord Jesus, where students are brought to meet personally with the Lord Jesus who is the only one. Lord and Savior, and experience His likeness. In carrying out Christian education in Christian schools, various disciplines are needed, including psychology. Psychology is the science of psychology that studies the unobservable inner state and observable outer state. Psychological principles that do not contradict the Bible are God's general revelations and can be used in Christian education in Christian schools. In terms of vision and mission in Christian schools, psychology can help to formulate a vision and mission that is biblical and responds to the needs of the times. In terms of the curriculum in Christian schools, psychology can help to discover new subjects and integrate all subjects with the Bible. In the case of teachers in Christian schools, psychology can aid in teacher recruitment, training, and evaluation. In the case of students in Christian schools, psychology helps to map out the uniqueness of each student and approach students personally. In terms of facilities in Christian schools, psychology helps to provide educational and innovative play tools according to the Bible